(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
In commercial banks, on the basis of capital attraction and improvement, it covers the need for monetary resources to carry out asset operations, primarily credit operations. Their role is very large and makes up more than 70% of the bank’s resources. By using the temporary free funds of legal entities and individuals, commercial banks meet the needs of the national economy and the population for additional working capital, and help turn money into capital. Banks have limited opportunities to attract funds, and in all countries this process is regulated by the Central Bank. The borrowed funds make up the main part of the credit resources of commercial banks